2020
DOI: 10.3390/agriculture10020044
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of ICT-Based Information Sources and Market Participation among Smallholder Livestock Farmers in South Africa

Abstract: The study explored the contribution of information and communication technology (ICT)-based information sources to market participation among smallholder livestock farmers. Use of ICTs is considered paramount for providing smallholder farmers with required market information, and also to reduce market asymmetries. A double hurdle regression was utilized to analyze data collected from 150 smallholder livestock farmers in the study area. The results show that while use of ICT-based market information sources sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 27 publications
6
16
0
Order By: Relevance
“…Stakeholders belonging to developing countries, small holders, and laborers expressed some difficulties in the use and availability of agricultural ICTs. These findings are in agreement with those of other previous studies that reported the importance of supporting vulnerable groups, specifically in developing countries (South Africa [26], Sub-Saharan Africa [27], and China [46]), and how such support can ensure the transformation and integration of digital technologies necessary for readiness and innovation process [46].…”
Section: Relationship Between Role/position In the Farm And The Role ...supporting
confidence: 93%
See 1 more Smart Citation
“…Stakeholders belonging to developing countries, small holders, and laborers expressed some difficulties in the use and availability of agricultural ICTs. These findings are in agreement with those of other previous studies that reported the importance of supporting vulnerable groups, specifically in developing countries (South Africa [26], Sub-Saharan Africa [27], and China [46]), and how such support can ensure the transformation and integration of digital technologies necessary for readiness and innovation process [46].…”
Section: Relationship Between Role/position In the Farm And The Role ...supporting
confidence: 93%
“…Despite the existing barriers to the use of agricultural ICTs, a growing body of evidence shows that the progress of agricultural ICT access is a key enabler of agricultural sector change. Several studies have shown the acceptability of farmers, specifically those belonging to developing countries and/or having small-scale agribusinesses, to transform into digital agriculture and the use of agricultural ICTs to improve their agribusiness outputs [26][27][28].…”
Section: Methodsmentioning
confidence: 99%
“…A variety of research-utilizing household data have sought to explain the factors that influence smallholder decisions regarding investing in livestock markets (Hagos et al, 2019;Kyaw et al, 2018;Musemwa et al, 2010;Nwafor et al, 2020). A literature review shows contradictory proof of factors impacting the marketing of livestock markets, such as environmental, political, human, and institutional influences.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of agricultural development, information and communication technologies have played an important role in developing countries. ICTs are proving new approaches for communicating and sharing the information among livestock farmers (15,16) to improve their knowledge and skills. Among modern ICTs, mobile phones serve as a means for effective transfer of knowledge and information about agricultural market and technology to farmers that enable them to apply the knowledge directly to improve their farming output and make easy access to market (17).…”
Section: Discussionmentioning
confidence: 99%